KECERDASAN EMOSIONAL IBU MENDIDIK ANAK DAN PRESTASI BELAJAR ANAK, PERAN SELF-EFFICACY SEBAGAI VARIABEL INTERVENING - Ni Luh Putu Sariani; Anak Agung Istri Agung Maheswari; I Nyoman Mustika; Ni Made Satya Utami (Forum Manajemen STIMI Handayani Denpasar, 2021)
The purpose of the research is: analyzing the effect of mother's emotional intelligence on self-efficacy, analyzing the influence of mother's emotional intelligence on children's learning achievement, analyzing the effect of self-efficacy on children's learning achievement, and analyzing the role of the intervening variable self-efficacy in relation to mother's emotional intelligence on children's learning achievement. A sample of 150 respondents were from the city of Denpasar with data analysis techniques, namely Partial Least Square approach (PLS). PLS is a component or variant based Structural Equation Modeling (SEM) equation. Based on the hypothesis testing that has been done, it can be found that maternal emotional intelligence has a significant positive effect on selfefficacy, mother's emotional intelligence has a significant positive effect on children's learning achievement, self- efficacy has a significant positive effect on children's learning achievement, and self-efficacy is able to be significant as an intervening variable in the proposed model.